An updated key to the genus Limnophora Robineau-Desvoidy (Diptera: Muscidae) from China, with descriptions of two new species - Du, Bintao; Liu, Xiaoyan; Yang, Ding (Zootaxa, 2023)
A key to the 80 species and 2 subspecies of the genus Limnophora Robineau-Desvoidy, 1830 from China based on males is provided, including two new species Limnophora magnipulvilla sp. nov. and Limnophora apiciflata sp. nov. Photographs of habitus and male genitalia as well as illustrations of the male genitalia of the new species are given.